Fundamental Study of Electromagnetic Actuated Needle-Free Jet Injection - Sripanagul, Gittiphong; Matthujak, Anirut (International Journal of Engineering and Technology, 2018)
The objective of this paper is to preliminarily study the needle-free jet injection by electromagnetic actuator. The jets were generated by electromagnetic actuator, being designed and manufactured for this study. Effects of orifice diameter of the nozzle, travelling distance, voltage and liquid volume on jet velocity and impact pressure were investigated by laser beam interruption method and PVDF pressure sensor respectively. Moreover, the evolution of jet penetration during the injection into 20% Polyacrylamide gel was visualized by high-speed video camera. It was found that the electromagnetic actuator with the orifice diameter of 0.2 mm at travelling distance of 5 mm and voltage of 500 Volt at all liquid volumes can be applied for needle-free jet injection. The introductory channel as well as circular Â Â Â Â Â Â dispersion was obviously observed seen from the evolution of jet penetration into 20% Polyacrylamide gel.Â Â